Persistence and pathogenicity of a native isolate of Leptolegnia chapmanii against Aedes aegypti larvae in different anthropic environments - Rueda Páramo, Manuel Enrique (2015)
The oomycete Leptolegnia chapmanii has been identified as a potential control agent of the primary vector of dengue, Aedes aegypti. In our assays, the persistence and pathogenicity of a native isolate of L. chapmanii decreased over time regardless of location. However, the mortality of Ae. aegypti larvae was significantly lower (p < 0.05) in containers located outside without sun protection (89% at first week and 9% at sixth week) compared with the containers located indoors (97% at first week and 42% at sixth week) and outside with shade (89% at first week and 29% at sixth week) possibly because of exposure to sun radiation.